North Korean art : the enigmatic world of Chosonhwa - Muhn, BG, 1954- (Irvine, CA : Seoul Selection U.S.A., 2019)
"This book is dedicated to the people of the Korean Peninsula and seeks to shed light on an area of art history that has long been virtually unknown and unseen. It is a collection of visual information focusing on chosonhwa, the North Korean name for traditional ink wash painting on mulberry paper. At the same time, it is the product of a deep exploration within the history and culture of North Korean, South Korean, and Chinese art"--
The Chosen Medium of Collaborative Paintings -- Notable Chosonhwa Collaborative Paintings -- Chapter VI-Contemporary Literati Painting -- Un Bong"" Ri Jae Hyon and His Art -- The Un Bong Portfolios -- Conclusion -- Bibliography -- Index -- Back Cover
Online resource; title from digital title page (viewed on September 08, 2020).
eBooks on EBSCOhost
Keywords: Painting, Korean -- Korea (North) -- 20th century; Artists -- Korea (North); Art, Korean -- Korea (North) -- 20th century; Art and state -- Korea (North); Socialist realism in art -- Korea (North); Peinture coréenne -- Corée du Nord -- 20e siècle.; Artistes -- Corée du Nord; Art coréen -- Corée du Nord -- 20e siècle.; Art -- Politique gouvernementale -- Corée du Nord; Réalisme socialiste dans l'art -- Corée du Nord; Criticism & Theory; ART; Art and state; Art, Korean; Artists; Painting, Korean; Socialist realism in art; Korea (North); 1900-1999